Relationship Among Chlorine Dose, Reaction Time and Bromide Ions on Trihalomethane Formation in Drinking Water Sources in Istanbul, Turkey - Özdemir1, K.; Toröz2, I.; Uyak3, V. (Asian Journal of Chemistry, 2014)
We investigate the effects of factors such as chlorine dose, reaction time and bromide ions on the formation and speciation of trihalomethanes during the chlorination of Istanbul reservoirs such as Terkos lake water, Büyükçekmece lake water and Ömerli lake water. The experimental results showed that approximately 50 % of trihalomethane formation was observed in the first 4 h of reaction time in chlorinated Terkos lake water, Büyükçekmece lake water and Ömerli lake water, respectively. Trihalomethane concentrations increased with increasing chlorine dosage and reaction time. Chloroform was the major trihalomethane species forming as a result of the chlorinated raw water samples. On the other hand, bromide ions play a great significant role in the distribution of trihalomethane species. The bromine and chlorine incorporation ratios were strongly related to natural organic matter precursors and bromide levels in Terkos lake water, Büyükçekmece lake water and Ömerli lake water. The percentage of bromine incorporation was much higher than that of chlorine in all chlorinated water samples.